Vesicular trafficking to the immune synapse: how to assemble receptor-tailored pathways from a basic building set - Anna eOnnis (Frontiers in Immunology, 2016)
The signals that orchestrate T-cell activation are coordinated within a highly organized interface with the antigen presenting cell (APC), known as the immune synapse (IS). IS assembly depends on T-cell antigen receptor (TCR) engagement by a specific peptide antigen-major histocompatibility complex (pMHC) ligand. This primary event leads to polarized trafficking of receptors and signaling mediators associated with recycling endosomes to the cellular interface, which contributes to IS assembly as well as signal termination and favours information transfer from T cells to APCs. Here we will review recent advances on the vesicular pathways implicated in IS assembly and maintenance, focusing on the spatiotemporal regulation of the traffic of specific receptors by Rab GTPases. Based on accumulating evidence that the IS is a functional homologue of the primary cilium, which coordinates several central signaling pathways in ciliated cells, we will also discuss the similarities in the mechanisms regulating vesicular trafficking to these specialized membrane domains.